Evaluating the relationship between bone density, osteoporosis, and some risk factors - Nguyen, Tran Thua; Uyen, Le Thi Ngoc; Phương, Phan Thị Minh; Tú, Trần Thị Cẩm; Huệ, Nguyễn Thị (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objectives: Evaluate the relationship between bone mineral density, osteoporosis, and certain risk factors such as age, body mass index, lifestyle, glucocorticoid use in the study subjects. Methods: A cross-sectional descriptive study was conducted on 142 elderly men who attended health check-ups at Hue Central Hospital from April 2023 to August 2024. Bone density was measured using Dual Energy X-ray Absorptiometry (DEXA) at three sites: lumbar spine, femoral neck, and total femur. Results: The prevalence of osteoporosis and osteopenia was 32.4% and 38.0%, respectively. Multivariate logistic regression analysis identified several factors significantly associated with osteoporosis. At the lumbar spine, increasing age (OR = 1.06), smoking (OR = 5.81), physical inactivity (OR = 3.42), and glucocorticoid use (OR = 29.10) were associated with a higher risk of osteoporosis. At the femoral neck, lower BMI (OR = 0.84 per 1 kg/m² increase) and smoking (OR = 3.48) were significantly associated with increased osteoporosis risk. Conclusions: Age, smoking, physical activity, BMI, and glucocorticoid use significantly affect bone density and osteoporosis in elderly men. Older age, smoking, lack of physical activity, and glucocorticoid use are linked to low bone density, especially at the lumbar spine. Higher BMI helps protect against osteoporosis, particularly at the femoral neck. Early screening, lifestyle changes, and proper medication management are essential to improving bone health and reducing fracture risk in elderly men.